Explorando a estrutura de nanoclusters de titânio (até 10 átomos) e os encapsulamentos em nanotubos de carbono - Umar Lucio Esper Mucelli Rezende (2019)
Clusters are particle aggregates that may span very different properties depending on their size. They may resemble properties of individual atoms or molecules, to properties observed at the bulk material. Due to this distinction in properties, clusters can be considered a new class of materials attracting wide interest within the scientific community. The hypersurface of titanium clusters, smaller than 10 atoms, was explored using an genetic algorithm coupled with GAMESS-US computational quantum chemistry package to make DFT-level energy evaluation with B3LYP exchange-correlation functional. This approach was used with the intention to generate initial structures unbiased, as opposed of using empirical potentials. The global minima obtained with this approach was refined, still at DFT-level, with ORCA but with DEF2-TZVP basis set as they provide more accurate results. The functional and basis set was validated using experimental reference data for Ti dimer. It has been found that the global minima cluster structures almost always exhibit a distorted shaped and high spin multiplicity. A fractional occupation number weighted electron density (FOD) analysis was performed in these clusters with the objective to evaluate the electronic correlation of the system, proving that it has strong static correlation further validating our methodology. Due to high computational cost, we choose only Ti3 and Ti4 to study how they would interact and affect carbon nanotubes structure and properties after being encapsulated. The Ti 3 cluster incapsulated in the carbon nanutube armchair (5,5)(with 15 and 7 Å of length and diameter respectively) did only an electrostatic interaction with the nanotube without promoting major structural or electronic changes, on the other hand, Ti4 increased the metallic character of the nanotube, observed by the reduction of 0.38 eV in the HOMO-LUMO gap for the inclusion compound Ti4NTC, as well as changes in the graphitic structure of the nanotube, by the reduction of D-band intensity in the Raman spectrum of the compound Ti4@NTC relative to the pure nanotube. Preliminary studies indicates that the encapsulation of titanium clusters can generate new materials, for example with more efficient electrochemical properties.